The Effect of Different Types of Aggregate and Additives on the Properties of Self-Compacting Lightweight Concrete (Journal of Engineering, 2012)
The major aim of this research is study the effect of the type of lightweight aggregate (Porcelinite and Thermostone), type and ratio of the pozzolanic material(SF and HRM) and the use of different ratios of w/cm ratio(0.32 and 0.35) on the properties of SCLWC in the fresh and hardened state. SF and HRM are used in three percentage 5%,10%, and 15% as a partial replacement by weight of cement for all types of SCLWC. The requirements of self-compatibility for SCC are fulfilled by using the high performance superplasticizer (G51) at 1.2liter per 100 kg of cement. The values of air dry density and compressive strength at age of 28 days within the limits of structural lightweight concrete. The air dry density and compressive strength at age of 28 days for w/cm ratio(0.32) for SCLWC of Porcelinit aggregate are 1964 kg/m3 and 29.57 MPa, respectively. The corresponding values for the SCLWC of Thermostone aggregate are 1820 kg/m3 and 25.75 MPa, respectively. The results show that the HRM performance which is locally available is better than SF in production of SCLWC.